Environmental evaluation of the sanitary landfill for the historic sanctuary of Machu Picchu and surrounding towns - Villafuerte, Iris (2004)
The environmental evaluation of the Sanitary Fill for the historical Sanctuary of Macchu-Picchus Project has been carried out, located in the Quebrada Yuncacha Huayco in front of Yanahuara, province of Maras, Department of Cuzco, 57 km. far from the city of Cuzco. First of all, an environmental diagnostic of the project area is made, identifying all aspects related to the areas flora, fauna, soil, climate and risks facing natural disasters. Moreover, the results of the survey on the populations points of view facing the project are presented. The main impact that such an activity would have will be described as well, considering implementation, operation, closing and post-closing stages. For that aim, a combination matrix is presented, interrelating both environmental categories with the project various activities, and environmental management plans. Finally, mitigation alternatives to environmental impacts generated by the sanitary fill are provided.